Influence of peripheral vascular calcification on efficiency of screening tests for peripheral arterial occlusive disease in diabetes—a cross‐sectional study. Issue 2 (11th September 2013) - Aubert, C. E.; Cluzel, P.; Kemel, S.; Michel, P.‐L.; Lajat‐Kiss, F.; Dadon, M.; Hartemann, A.; Bourron, O.
Abstract Aims Pulse palpation and ankle brachial index are recommended to screen for peripheral arterial occlusive disease in people with diabetes. However, vascular calcification can be associated with false negative tests (arteriopathy present despite normal screening tests). We therefore studied the impact of peripheral vascular calcification on the performance of these tests. Methods This cross‐sectional study included 200 people with diabetes at high risk of cardiovascular disease. The main exclusion factor was an estimated glomerular filtration rate < 30ml/min. Peripheral arterial occlusive disease was diagnosed by colour duplex ultrasonography and peripheral vascular calcification scored by computed tomography scan. We measured sensitivity, specificity, predictive values, accuracy and likelihood ratios of pulse palpation and ankle brachial index, and looked for the impact of calcification on false negative tests (arteriopathy present despite normal screening tests). Results Ankle brachial index alone had poor sensitivity and negative predictive value and high negative likelihood ratio. Pulse palpation had higher sensitivity and negative predictive value. An abnormal pulse palpation, defined by weak or missing pulses, combined with an abnormal ankle brachial index, had the highest sensitivity and negative predictive value (92.3 and 89.8%, respectively). Vascular calcification score was higher in patients with false negative tests, for both pulse palpation and ankle brachial index (P < 0.0001 for all). Ankle systolic blood pressure was higher in patients with false negative tests for pulse palpation (P = 0.004). Conclusions Below‐knee vascular calcification gave a high rate of false negative results for ankle brachial index. Refined pulse palpation combined with ankle brachial index remained the best strategy to screen for peripheral arteriopathy.